Analisis Framing Pada Media Pemberitaan Kompas.Com Dan CNNIndonesia.Com Terkait Batas Usia Capres- Cawapres 2024 - Annisa Adilla; Rizky Rahmanda Irawan; Diryo Suparto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This article examines the constitutional deviation of the age limit for presidential and vice presidential candidates in 2024 in two news media, Kompas.com and CNNIndonesia.com. The research uses Robert Entman's four framing elements and 21 news articles from Kompas.com and CNNIndonesia.com. Results show Kompas.com raises issues supporting Anwar Usman's vice presidential nomination, while CNNIndonesia.com addresses deficiencies in the decision sent by Usman, resulting in eight judges rejecting changes in age limit requirements.